Explicație pas cu pas:
a)
[tex]AD = \sqrt{ {(2 - 2)}^{2} + {(2 - ( - 2))}^{2} } = \sqrt{16} = 4 \\ [/tex]
[tex]BC = \sqrt{ {(7 - 7)}^{2} + {(7 - 3)}^{2} } = \sqrt{16} = 4 \\ [/tex]
AD ≡ BC
[tex]x_{A} = x_{D} \: si \: x_{B} = x_{C} \implies AD || BC[/tex]
=> ABCD paralelogram
b)
[tex]AE = \sqrt{ {(2 - ( - 4))}^{2} + {(2 - 0)}^{2} } = \sqrt{36 + 4} = \sqrt{40} \\ DE = \sqrt{ {(2 - ( - 4))}^{2} + {( - 2 - 0)}^{2} } = \sqrt{36 + 4} = \sqrt{40} \\ BF = \sqrt{ {(7 - 13)}^{2} + {(7 - 5)}^{2} } = \sqrt{36 + 4} = \sqrt{40} \\ CF = \sqrt{ {(7 - 13)}^{2} + {(3 - 5)}^{2} } = \sqrt{36 + 4} = \sqrt{40} [/tex]
AE ≡ DE ≡ BF ≡ CF și AD ≡ BC
=> ΔBCF ≡ ΔADE, triunghiuri isoscele
q.e.d.